RNA-Seq Based Toxicity Analysis of Mesoporous Polydopamine Nanoparticles in Mice Following Different Exposure Routes - Huang, Zihua; Xie, Luoyijun; Zhang, Jifan; Li, Qiyan; Liu, Yulin; Fu, Xuemei; Yuan, Miaomiao; Li, Qingjiao (Frontiers in Bioengineering and Biotechnology, 2022)
Mesoporous polydopamine nanoparticles (MPDA NPs) are promising nanomaterials that have the prospect of clinical application for multi-strategy antitumor therapy, while the biosecurity of MPDA NPs remains indistinct. Here, transcriptome sequencing (RNA-Seq) was performed to systematically reveal the toxicity of MPDA NPs to five categories of organs after three different exposure routes, including intravenous injection, intramuscular injection, and intragastric administration. Our results uncovered that MPDA NPs could be deposited in various organs in small amounts after intravenous administration, not for the other two exposure routes. The number of differentially expressed genes (DEGs) identified in the heart, liver, spleen, lung, and kidney from the intragastric administration group was from 22 to 519. Similarly, the corresponding number was from 23 to 64 for the intramuscular injection group and was from 11 to 153 for the intravenous injection group. Functional enrichment analyses showed 6, 39, and 4 GO terms enriched for DEGs in intragastric administration, intramuscular injection, and intravenous injection groups, respectively. One enriched pathway was revealed in intragastric administration group, while no enriched pathway was found in other groups. Our results indicated that MPDA NPs produced only slight changes at the transcriptome level in mice, which provided new insights for further clinical application of MPDA NPs.